Situation Analysis of Infectious Hazardous Waste Management from the Community During the Covid-19 Pandemic in Indonesia - Monica Djaja Saputera; A. Joko Purwoko; Edward Kurnia Setiawan Limijadi (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract : The increasing anticipation of the public in using disposable masks during the COVID-19 pandemic, was not followed by proper waste management efforts. Disposable medical masks are one source of infectious B3 waste that needs to be processed in an appropriate way to prevent transmission and control the spread of COVID-19. The lack of information and procedures for managing infectious B3 waste from the government to the community and the uneven supply and distribution of dropboxes or depots to collect infectious B3 waste from the community is a problem that requires an appropriate and fast solution from the government.Keywords: COVID-19, medical B3 waste, masks, medical masks